Risk of Nonunion Associated with NSAID Use Following Partial Wrist Fusion: A Retrospective Analysis - Smith, Kira L.; Eghtedari, Cyrus F.; Berk, Alexander N.; Good, Logan; Malone, Kevin J.; Abola, Matthew V. (Journal of Wrist Surgery, 2025)
The purpose of this investigation was to assess whether the use of nonselective nonsteroidal anti-inflammatory drugs (NSAIDs) or selective cyclooxygenase-2 (COX-2) inhibitors in the perioperative period is associated with the risk of nonunion after partial wrist fusion. We hypothesized that exposure to nonselective NSAIDs or selective COX-2 inhibitors would not increase the rate of nonunion after partial wrist fusion when compared with control cohorts.The TriNetX U.S. Collaborative database was queried using Current Procedural Terminology (CPT) and International Classification of Diseases, 10th Revision (ICD-10) codes to identify patients aged 18 and older who underwent partial wrist fusion between 2008 and 2023. Patients were stratified according to the chronicity and type of NSAID use, including chronic NSAID use (within 90 days of surgery), acute NSAID use (within 30 days of surgery), perioperative ketorolac (Toradol) use (within 24 hours of surgery), and selective COX-2 inhibitor use (within 30 days of surgery). The cohorts were propensity-matched by age, gender, race, ethnicity, body mass index (BMI; kg/m2), and presence of type 2 diabetes mellitus. The risk of nonunion, defined as the need for revision fusion, conversion to total wrist arthrodesis, or conversion to total wrist arthroplasty, was assessed within the 1-year postoperative period. Chi-square analyses were used to compare the rate of nonunion for each cohort. Statistical significance was determined to be a p-value <0.05.A total of 3,073 patients undergoing partial wrist fusion were identified, of which 2,072 had a documented history of perioperative NSAID use. After 1:1 propensity score matching, the cohorts included 1,148 patients in the chronic NSAID group, 889 in the acute NSAID group, 482 in the Toradol group, and 140 in the COX-2 inhibitor group. The rate of nonunion was significantly higher in patients exposed to NSAIDs within 30 days of surgery (5.96%) compared with the control cohort (3.04%; p = 0.003). However, chronic exposure to NSAIDs or perioperative Toradol was not associated with a higher rate of nonunion (p = 0.17 and p = 0.56, respectively). Additionally, use of selective COX-2 inhibitors versus nonselective COX-2 inhibitors had no significant impact on the rate of nonunion (p = 0.66).Patients exposed to NSAIDs within 30 days of a partial wrist fusion had an increased risk of nonunion when compared with a control cohort. Acute use of NSAIDs may be a risk factor for impaired bone healing after partial wrist fusion, and their use should be carefully considered in high-risk patients.
Keywords: partial wrist arthrodesis; four-corner fusion; nonsteroidal anti-inflammatory drugs; selective COX-2 inhibitors; nonunion